Native and foreign born as predictors of pediatric asthma in an Asian immigrant population: a cross sectional survey - Woodin Mark; Lee Angela C; Brugge Doug; Rioux Christine (BMC, 2007)
Abstract Background Asthma prevalence is lower in less developed countries and among some recent immigrant populations in the US, but the reasons for this are not clear. One possibility is that early childhood infections are protective against asthma. Methods We surveyed Asian immigrant children (n = 204; age 4-18) to assess the relationship between asthma and native or foreign place of birth. We included questions about environmental exposures, demographic variables and family history of asthma to test whether they might explain effects of place of birth on asthma. Results The native and foreign born groups were similar in most respects. Analysis of association with diagnosed asthma for all ages together resulted in two logistic regression models. Both retained born in the US (ORs were 3.2 and 4.3; p < 0.01) and family history of asthma (ORs were 6.4 and 7.2; p < 0.001). One model retained living near heavy motor traffic (OR = 2.6; p = 0.012). The other retained language (OR = 3.2; p = 0.003). However, for older children (11-18 years of age) being born in the US lost some of its predictive power. Conclusion Our findings are consistent with early childhood infections that are prevalent outside the US protecting against asthma.